La relación población-recursos en la periferia urbana. Una experiencia teórico-metodológica - Salazar Cruz, Clara Eugenia (El Colegio de México A.C., 2000)
This article has a two-fold aim. First, to show that research is a continuous process of learning, particularly when one is dealing with areas of knowledge for which there is no specific disciplinary tradition, as in the case of environmental studies from a social science perspective. Second, to show, using a practical example, that this process is not a linear practice but a two-way process in which theoretical-methodological elements are constructed, discarded and reinterpreted until they create a coherent body of interpretation. That is why this article has not been organized in a conventional fashion and instead, follows a process of presenting ideas, raising questions, defining and redefining the routes to be followed and showing the difficulties faced from the initial conception of the idea to the application and interpretation of empirical work, passing through the development of a theoretical-methodological strategy. This is illustrated by an exploratory study on the relationship that the common-land owners of San Nicolás Totolapan, now mainly acknowledged as ejido owners of the same name, have established with the natural resources of their ejido, located on the southern periphery of Mexico City.